Exploring the Archaeome: Detection of Archaeal Signatures in the Human Body - Pausan, Manuela R.; Csorba, Cintia; Singer, Georg; Till, Holger; Schöpf, Veronika; Santigli, Elisabeth; Klug, Barbara; Högenauer, Christoph; Blohs, Marcus; Moissl-Eichinger, Christine (Frontiers in Microbiology, 2019)
Due to their fundamentally different biology, archaea are consistently overlooked in conventional microbiome surveys. Using amplicon sequencing, we evaluated methodological set-ups to detect archaea in samples from five different body sites: respiratory tract (nasal cavity), digestive tract (mouth, appendix, and stool) and skin. With optimized protocols, the detection of archaeal ribosomal sequence variants (RSVs) was increased from one (found in currently used, so-called ‘universal’ approach) to 81 RSVs in a representative sample set. The results from this extensive primer-evaluation might not only prove useful for analyzing the human archaeome in more detail but could also be used for other holobiont samples.